Dejetos de suínos como fonte protéica alternativa para alevinos de Piauçu ( leporinus macrocephalus ): reciclagem de nutrientes e diminuição do impacto ambiental no entorno das criações de suínos - Garcia, Luciene de Moraes (2009)
One experiment was carried out to study the use of swine feces in fish diets as a practical alternative that could be used by swine farmers to reduce environment pollution as well as increase the profitability of the farm. Dry finishing swine feces were analysed and added to a starter fish diet at levels of 0, 10, 20 and 30% on isocaloric and isoproteic diets. Diets were formulated, moistured with hot water and processed in a meat grinder to agglutinate the particles and dried in a air forced oven at 65º C. The diets were fed to four groups of 30 piauçu (Leporinus macrocephalus) fingerlings, initial weight of 0,90 ± 0.10 g, for 65 days. Feed was supplied three times a day at the rate of 10% of reservoir's biomass. Fingerlings were kept in 16 one thousand liters reservoirs, The water quality of these reservoirs was monitored daily by physical and chemical analysis. No differences (P > 0.01) in performance were observed. However, the diet with 10% of dry swine feces produced the best numerical performance showing that the dry swine feces has potential as a feed ingredient in fish diets. The analysis of fish carcass at the end of the experiment showed that as the level of swine feces increased in the diet the level of carcass lipids was reduced. There were no effect of diets on the fish carcass protein and ash. These results showed that the dry swine feces may be used as an ingredient in balanced diet for Leporinus macrocephalus and also help to reduce the environmental impact of swine farming pollution. Therefore, these results show an alternative to improve quality of life and also fish farming in the areas of high intensive swine production.